Value of brain tissue oxygen saturation in neonatal respiratory distress syndrome: a clinical study - Keping Cheng; Huijie Zhu; Zikai Zhou; Weiyuan Chen; Aijuan Yang (PAGEPress Publications, 2024)
Neonatal respiratory distress syndrome (NRDS) is one of the major causes of pre-term mortality and morbidity among very-low-birth-weight infants (VLBWI) in low- and middle-income countries (LMIC). Some of the neonates pass away despite admission and care in intensive care units (ICUs). The present clinical trial seeks the application value of elevating oxygen saturation in the brain cells of pre-term neonates born with NRDS. Near-infrared spectroscopy (NIRS) was used to monitor the neonates' microscopic cerebral oxygenation levels do determine hemoglobin concentration in brain tissues, whereas the pulse oximetry was used to measure oxygenation levels among the patients. In statistical analyses, the Analysis of Variance (ANOVA), and descriptive statistics was deployed in the Jupyter Notebook environment using Python language. High saturation of oxygen in the brain tissues result in important biological and physiological processes, including enhanced oxygen supply to cells, reduced severity of NRDS, and balancing oxygen demand and supply. The correlations of oxygen saturation with systemic saturation of oxygen, the saturation of oxygen in brain tissues, the association between brain-specific and systemic saturation, and the impact of these outcomes on clinical practices were deliberated. Also, the pH gas values, the saturation of oxygen in neonates' brain tissues, metabolic acidosis, the effect of acid-base balance and cerebral oxygen supply, and the oxygenation of brain tissues and the pH values emerged as important variables of oxygenation of brain tissues in pre-term neonates. Oxygen saturation in brain cells influence vital physiological and biological processes. Balancing acid-base saturation or levels is needed despite the challenging achievement. Oxygenation of brain tissues improve the brain's overall functioning.